NARRATIVE STYLE IN THE STORY OF “THROUGH THE TUNNEL” BY DORIS LESSING (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The Article was dedicated to convey narrative style of “through the tunnel” story. Third-person narration is used in "Through the Tunnel" by Doris Lessing. The narrator, who is not involved in the story's storyline, describes the events from a variety of characters' points of view. Apart from that I decribed about language and characters of the story